2021
DOI: 10.1098/rspb.2021.0325
|View full text |Cite
|
Sign up to set email alerts
|

Emerging themes in Population Consequences of Disturbance models

Abstract: Assessing the non-lethal effects of disturbance from human activities is necessary for wildlife conservation and management. However, linking short-term responses to long-term impacts on individuals and populations is a significant hurdle for evaluating the risks of a proposed activity. The Population Consequences of Disturbance (PCoD) framework conceptually describes how disturbance can lead to changes in population dynamics, and its real-world application has led to a suite of quantitative models that can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 133 publications
2
25
0
Order By: Relevance
“…We showed that the consequences of environmental change alone could be much more severe than those of localized sources of disturbance, such as military sonar, but the patterns of individual exposure in space and time are critical to determine the magnitude of any effect. Overall, these results contribute to the accumulating evidence that the population consequences of anthropogenic disturbance are influenced by a species' life history and ecology, and how these interact with the features of the disturbance source (Keen et al., 2021). We presented an example of how predictive mechanistic tools, developed using lessons and data from many diverse fields, can inform management decisions so that they minimize risks for wildlife populations, direct the monitoring of ongoing effects and highlight key data required to reduce uncertainties.…”
Section: Discussionsupporting
confidence: 57%
“…We showed that the consequences of environmental change alone could be much more severe than those of localized sources of disturbance, such as military sonar, but the patterns of individual exposure in space and time are critical to determine the magnitude of any effect. Overall, these results contribute to the accumulating evidence that the population consequences of anthropogenic disturbance are influenced by a species' life history and ecology, and how these interact with the features of the disturbance source (Keen et al., 2021). We presented an example of how predictive mechanistic tools, developed using lessons and data from many diverse fields, can inform management decisions so that they minimize risks for wildlife populations, direct the monitoring of ongoing effects and highlight key data required to reduce uncertainties.…”
Section: Discussionsupporting
confidence: 57%
“…The population consequences of disturbance (PCoD) conceptual framework describes how disturbance-induced changes in individual behaviour and physiology can affect population dynamics by compromising the health status of an individual, and thus its ability to survive and reproduce successfully (see review in Pirotta et al, 2018b ). While health encompasses multiple aspects of an individual’s physiological status, most PCoD implementations to date have focused on the changes in a female’s time-energy budget and the consequences on her ability to sustain the costs of maintenance (and thus survival) and reproduction ( Keen et al, 2021 ; Pirotta et al, 2018b ). Bioenergetic models represent an ideal tool to mechanistically capture this energetic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes have clear bioenergetic implications for marine mammals and the ecosystems they inhabit ( Costa, 2008 ; Laidre et al, 2020 ; Gallagher et al, 2022 ). Since the prey landscape is a major driver of the spatiotemporal distribution of marine mammals ( Sveegaard et al, 2012 ; Zerbini et al, 2016 ; Sigler et al, 2017 ; Straley et al, 2018 ; Pendleton et al, 2020 ), knowledge of prey fields and how they may be changing provides insight into the potential impact of anthropogenic disturbances on energy budgets ( Keen et al, 2021 ). As such, prey fields are critical components of many PCoD models ( Nabe-Nielsen et al, 2018 ; Pirotta et al, 2019 ; McHuron et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%